Contribution to the knowledge of Ichneumoninae of Siberia and Far East Russia (Hymenoptera, Ichneumonidae) - Riedel, Matthias (Contributions to Entomology = Beiträge zur Entomologie, 2020)
In this survey, distributional records of 81 Ichneumoninae from Siberia and Far East Russia are given. 44 of them are newly reported from Siberia and/or Far East Russia and 25 species have not been found in the East Palaearctic region before. Eleven species are described as new: Aoplus ocellator spec. nov., Ectopius sibiricus spec. nov., Hoplismenus flagellator spec. nov., Ichneumon brevimaculatus spec. nov., Ichneumon flavocoxalis spec. nov., Ichneumon flavotibialis spec. nov., Ichneumon megextenorius spec. nov., Ichneumon pilocephalus spec. nov., Ichneumon taegeri spec. nov., Monontos baikalensis spec. nov. and Protichneumon nigriventris spec. nov. One taxon is described as a new subspecies: Chasmias paludator sibiricus subspec. nov. For Coelichneumon septenus Townes et al., 1965 a new female is described. The genus Monontos Uchida is transferred from the tribe Heresiarchini to the Ichneumonini. Nomenclatural acts Aoplus ocellator spec. nov. – urn:lsid:zoobank.org:act:48A8BD7B-482E-46DB-A330-DD5EEB39DE4C Ectopius sibiricus spec. nov. – urn:lsid:zoobank.org:act:AD4C044E-A817-41C5-B24B-83085E159819 Hoplismenus flagellator spec. nov. – urn:lsid:zoobank.org:act:675CC203-04A9-4B23-9247-880562A8B0C4 Ichneumon brevimaculatus spec. nov. – urn:lsid:zoobank.org:act:32A6E211-9DC7-4E78-A7C4-D7C1FD8F1A6C Ichneumon flavocoxalis spec. nov. – urn:lsid:zoobank.org:act: F0B7571F-F53D-4F5E-AEF7-E8E0DEC72F1D Ichneumon flavotibialis spec. nov. – urn:lsid:zoobank.org:act:07E8B9DD-3819-4F13-B988-5FAC6CBA25C3 Ichneumon megextenorius spec. nov. – urn:lsid:zoobank.org:act:3F921DA4-7285-4328-85AB-C32096485FA8 Ichneumon pilocephalus spec. nov. – urn:lsid:zoobank.org:act:FCB03748-C2BF-47B5-9439-397B6E944973 Ichneumon taegeri spec. nov. – urn:lsid:zoobank.org:act:2EFB6CDD-10E9-4D81-8639-D8E54F68DC08 Monontos baikalensis spec. nov. – urn:lsid:zoobank.org:act:FD6CE0F9-611F-4590-9511-6DBABF35EE9A Protichneumon nigriventris spec. nov. – urn:lsid:zoobank.org:act:98F723A9-B2A8-44D8-B118-83F88FAEAE7E